THE EFFECT OF VARIOUS SPAT COLLECTOR MATERIALS FOR SPAT ATTACHMENT OF PEARL OYSTER (Pinctada maxima) - Endang Arini; Nur Taufiq Syamsudin Putra Jaya (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Early stage development of pearl oyster spat was very critical, hence spat required suitable substrates for their settlement to complete their metamorphosis. In this stage, byssus for the attachment is vulnerable and easy to break if there are some disturbance e.g. water movement, hence spat easily falling onto the bottom layer which may have various dirt materials leading to the dead of the spat. In the pearl oyster culture spat collector is important. The aim of this study is to study the effect of different collector materials to the number of spat settled, to reveal the best collector materials and the endurance of spat at the collector. This study was conducted in PT Autore Pearl Culture, at Sumbawa island, Nusa Tenggara Province. Materials used in this research were collectors of different substance i.e. asbestos (A), bamboo (B), polyethylene and roof ceramic (D) substance. The method used was laboratories experiment with Completely Random Design by 4 treatments and 3 replications. Data taken were the number of spat settlement, endurance test, and water quality. Data tested with Analysis of Variance (ANOVA) and further tested with Duncan Duplicate Regional test. Water quality was analyzed descriptively. The results showed that different collector materials performed a high significantly difference (p<0.01) to the number of spat settled. The best settlement reached by polyethylene [106±3.61 ind. (dm2)-1] followed by bamboo [40±3.61 ind. (dm2)-1], asbestos [16±2.52 ind. (dm2)-1] and roof ceramic [15±3.61 ind. (dm2)-1]. The endurance test indicated that percentage of lowest detached of spat from collector reached by treatment B (10.23%), followed by C (11.12%), D (46.95%) and A (50.60%). Water qualities during study were appropriate for the life and growth of pearl oyster spat.